Association of body mass index with longitudinal rates of retinal atrophy in multiple sclerosis. (June 2020) - Filippatou, Angeliki G; Lambe, Jeffrey; Sotirchos, Elias S; Fitzgerald, Kathryn C; Aston, Andrew; Murphy, Olwen C; Pellegrini, Nicole; Fioravante, Nicholas; Risher, Hunter; Ogbuokiri, Esther; Kwakyi, Ohemaa; Toliver, Brandon; et al.
Background: Studies evaluating associations between body mass index (BMI) and optical coherence tomography (OCT) measures in multiple sclerosis (MS) are lacking. Objective: To assess whether elevated BMI is associated with accelerated retinal atrophy. Methods: In this observational study, 513 MS patients were followed with serial spectral-domain OCT for a median of 4.4 years. Participants were categorized as normal weight (BMI: 18.5–24.9 kg/m 2 ), overweight (BMI: 25–29.9 kg/m 2 ), and obese (BMI: ⩾30 kg/m 2 ). Participants with diabetes mellitus or uncontrolled hypertension and eyes with optic neuritis (ON) ⩽6 months prior to baseline OCT or during follow-up were excluded. Statistical analyses were performed with mixed-effects linear regression. Results: Obese patients ( n = 146) exhibited accelerated rates of ganglion cell + inner plexiform layer (GCIPL) atrophy relative to normal weight patients ( n = 214; –0.57%/year (95% confidence interval (CI): –0.65% to –0.48%) versus –0.42%/year (95% CI: –0.49% to –0.35%); p = 0.012). GCIPL atrophy rate did not differ between overweight ( n = 153) and normal weight patients (–0.47%/year vs –0.42%/year; p = 0.41). Each 1 kg/m 2 higher BMI was associated with accelerated GCIPL (–0.011%/year; 95% CI: –0.019% to –0.004%; p = 0.003) atrophy. Multivariable analyses accounting for age, sex, race, MS subtype, and ON history did not alter the above findings. Conclusions: Elevated BMI, in the absence of overt metabolic comorbidities, may be associated with accelerated GCIPL atrophy. Obesity, a modifiable risk factor, may be associated with accelerated neurodegeneration in MS.